A recursive algorithm to generate piecewise linear budget contraints - Alan Duncan; Graham Stark (Institute for Fiscal Studies (IFS), 2000)
This paper introduces a recursive algorithm with which to generate complete and accurate budget constraints using static microsimulation models. We describe the generic algorithm and discuss and extension by which reasons for any change in the marginal effective tax rate may be explained. We derive continuous expressions for average tax rate (ATR), average marginal tax rate (AMTR), replacement rate (RR) and marginal effective tax rate (METR) schedules, expressed solely in terms of the marginal wage rate and 'virtual' income. A practical application serves to highlight the usefulness of this algorithm in fiscal policy analysis at micro level.
Keywords: 330; Budgetrestriktion; Simulation; Theorie